Photographic Detection of Cadmium(II) and Zinc(II) Ions. (2016) - Lvova, Larisa; Di Natale, Corrado; Paolesse, Roberto; Giorgi, Luca; Fusi, Vieri; Garau, Alessandra; Lippolis, Vito
Abstract: The binding properties of two 2, 8-dithia-5-aza-2, 6-pyridinophane-based ligands, bearing respectively coumarin (HNCum) and naphthol-benzoxaazole (HNBO) optically active units as pendant arms, were studied with the aim of transition metal cations selective detection. The novel all-solid-state optodes were obtained by inclusion of fluorophores inside PVC-based polymeric films. The influence of lipophilic sites incorporation and plasticizer nature on pyridinophane-based optodes response was investigated. An enhanced selectivity of the ligands towards Cadmium(II) and Zinc(II) ions was detected. Light Emitting Diode, LED 380 nm, was used as light source, and a digital camera as a signal detector. The results obtained demonstrated the suitability of the developed optodes to perform fast and low cost simultaneous monitoring of Zn 2+ and Cd 2+ ions by means of familiar devices and chemometrics.